Actual epistemes of Ukrainian modern classical philology - Голубовська, Ірина Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
Within the framework of this article, the development of Ukrainian classical philology from 2006 to the present day in the context of changing scientific and linguistic paradigms, transition from traditional interdisciplinary descriptive approach to the structural one and, ultimately, to the cognitive-cultural and communicative-oriented perspective of Greek and Latin language phenomena. As a result of extralinguistic factors, in modern Ukrainian space of classical philology preference is given to linguistically oriented research, one might observe a gradual rejection from the broad humanitarian mode of research (with the traditional involvement of archeology, literature, history, culturology, semiotics, etc.), which creates its new face. On the grounds of generalization of the different research tools and metalanguage used in numerous researches in the field of classical philology in our times the conclusion was drawn about the integration of those traditional research approaches which had been practiced beginning from the XIV-th century, with those understandings that are currently characteristic of modern multi-vector theoretical linguistics with its various subject areas. Ukrainian classics successfully use in their studies the categorial apparatus of modern theoretical linguistics. They creatively apply those scientific and linguistic developments that are inherent in today’s anthropologically oriented linguistics.